(untitled) (European Journal of Language and Literature, 2015)
The object of this study is the relationship between the subjunctive mood and infinitive in the Albanian language. Subjunctive is one of the inherited moods in Albanian. Apart from the indicative, subjunctive is also widely used, because it expresses a variety of modal meanings. The frequency of subjunctive mood usage, mainly in the south dialect, is related to its use as a synonym to the infinitive. The subjunctive mood coincides with the non-finite forms, especially the infinitive. This coincidence is evident on the syntactic aspect and its functional point of view, as well. The synonymy of infinitive to the subjunctive is observed in the present standard Albanian language. In most of the infinitive uses, we can easily replace them with the subjunctive, without causing any changes in the modality or relationship with other syntactic units. This substitution is not always possible. This occurs in the category of subordinate or main clauses and simple sentences in the function of the simple predicate. Nevertheless, nowadays, we notice synonymy relationships between the subjunctive and infinitive, especially with the grammatical constructions that denote meanings of purpose. In the relative clauses, this synonymy is much more limited. Substitution of the infinitive with the subjunctive in such constructions can bring slight changes of meaning. Anyway, we should emphasize that despite the value of the infinitive, the subjunctive mood is widely used in the national literary language.